APPLICATION OF MATHEMATICAL MODEL FOR CALCULATING THE OPTIMAL NUMBER OF COTTON IN INVENTORY PT. XYZ USING MICROSOFT VISUAL BASIC 6.0 - Suyanti Suyanti; Sahni Damerianta , Skom, MMSi (Jurnal Sistem Informasi, 2005)
Determining the model is a necessity in a company, Total material consumption ofcotton is uncertain within a company can result in losses, the amount of inventorythat is too much compared to the amount needed would result in overlappinginventories and working capital investment means embedded and useless. In additioncotton is easy once the goods are damaged and if damaged can not be used again inother words should be discarded. Conversely, if the amount of inventory is notsufficient amount of the request or demand would cause interruption of theproduction process that can damage the company image in the eyes of the customer.Therefore, it needs an inventory model that is able to answer condition above, so indetermining the optimal model of cotton supply in PT. XYZ, where the use of cottoneach month is uncertain. Mathematical models is an approach that the authorsanalyzed for application at. PT. XYZ. With this mathematical model it can bedetermined the optimal amount of cotton supplies each month is also equipped with atable-making opportunity loss as consideration for decision making.